Study of phenol biodegradation in different agitation systems and fixed bed column: experimental, mathematical modeling, and numerical simulation - Ribeiro H.B. (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature.Phenol degradation was studied in two different agitation systems in a batc h reactor (mechanical agitation and orbital agitation) and the support of the most efficient system was used for fixed bed bioreactor studies. The support used was coconut shell charcoal. The results showed that the mechanical agitation bioreactor was more effective in phenol removal, due to the amount of biomass adhered to the support (8.56 mg gsupport−1), running at approximately 100% of the phenol biodegradation in 300 min. The toxicity analysis of the waters was moderate, because the EC50,48h values in the analyzed samples are higher than 50%. Within the experimental data obtained from the batch system, it was possible to find the parameters of the kinetic model of Michaelis-Menten, which was used to simulate the bioreactor in a fixed bed. A mathematical model of a one-equation, which considers the effects of dispersion, convection, and reaction in the liquid phase, and diffusion and reaction inside the biofilm was used and the results obtained through numerical simulation were compared with the experimental results of the bioreactor in a fixed bed, and new operational conditions in the bed were simulated with good accuracy.